Analisis Pendapatan Jual Beli Terhadap Profitabilitas dengan BOPO Sebagai Variabel Moderating : (Studi Bank Umum Syari’ah Indonesia) - Hanifah Hanifah; Haryadi, Bambang (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2025)
This research aims to determine the effect of sales/buying and selling income on profitability at Islamic commercial banks in Indonesia which is moderated by operational costs on operational income (BOPO). This research uses secondary data with a quantitative descriptive analysis method, which uses purposive sampling to determine the sample. Data collection methods through observation and documentation. The research results show that there is an influence of sales/buying and selling income on profitability (ROE) both before interacting with the moderating variable and after interacting. The difference is, before BOPO and the predictor variables interact, the effect is significantly positive, but after interacting the effect is significantly negative.